The sesame street library, v. 4 - Frith, Michael (New York : Funk and Wagnalls, 1978)
With Jim Henson's Muppets.
Contents: Featuring the letters G, H and I and the number 4.
Keywords: Alphabet; Number concept; Counting; Reading